2006
DOI: 10.1111/j.2042-3306.2006.tb05615.x
|View full text |Cite
|
Sign up to set email alerts
|

Double blind investigation of the effects of oral supplementation of combined glucosamine hydrochloride (GHCL) and chondroitin sulphate (CS) on stride characteristics of veteran horses

Abstract: Oral GHCL and CS supplementation may improve welfare by alleviating symptoms of degenerative joint disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 8 publications
1
13
1
2
Order By: Relevance
“…Thus, there is growing interest in nonpharmacologic approaches to ameliorate exercise-induced inflammation [36][37][38][39]. Various dietary supplements have been proposed to alleviate exercise-related injuries and illnesses [40][41][42][43][44][45][46][47][48][49][50]. Although many of these same compounds have been used in horses [37,[48][49][50][51][52][53][54][55][56][57][58], their effect on exercise-induced proinflammatory responses has not been investigated in detail [55].…”
Section: Introductionmentioning
confidence: 97%
“…Thus, there is growing interest in nonpharmacologic approaches to ameliorate exercise-induced inflammation [36][37][38][39]. Various dietary supplements have been proposed to alleviate exercise-related injuries and illnesses [40][41][42][43][44][45][46][47][48][49][50]. Although many of these same compounds have been used in horses [37,[48][49][50][51][52][53][54][55][56][57][58], their effect on exercise-induced proinflammatory responses has not been investigated in detail [55].…”
Section: Introductionmentioning
confidence: 97%
“…Also, recent studies have indicated that glucosamine sulfate possesses antioxidant properties, thereby, suppressing high concentrations of reactive oxygen species (ROS) which cause the breakdown of cartilage due to the presence of free radicals and pro-oxidants [33]. Also, in an animal study, range of joint motion increased significantly at the elbow joint with an increase in selected gait parameters following oral administration of glucosamine sulphate [34]. Previous reports had also established that drugs are detectable underneath site of application using transdermal administration techniques [35].…”
Section: Discussionmentioning
confidence: 99%
“…Lameness evaluations are fine, but for these data to provide meaningful insight into the biological effect of GBN on horses, they must be supported by objective outcome measures, within a context of experimental blinding. These may include synovial fluid and/or serum analyses for biomarkers of inflammation and/or cartilage metabolism (White et al 1994;Fenton et al 1999;Caron et al 2002;Verde et al 2006;Meulyzer et al 2008Meulyzer et al , 2009Pearson et al 2009), objective measures of gait analysis (Clayton et al 2002;Forsyth et al 2006), and/or imaging techniques, including radiographs (Hanson et al 2001), ultrasound, arthroscopy or nuclear scintigraphy.…”
Section: 'Power' In Persuasionmentioning
confidence: 99%
“…Another common problem with studies evaluating GBN for horses was the lack of an appropriate placebo control. In some cases placebo controls were not used at all (Hanson et al 1997;Rodgers et al 2006) but, more frequently, the use of a placebo was reported but the composition not provided (Hanson et al 2001;Forsyth et al 2006;Verde et al 2006;Keegan et al 2007). Without this information, it is impossible for readers to determine if the dietary treatment was compared against an inert product as intended, or a product which might influence outcome measures in some way.…”
Section: Experimental Controlsmentioning
confidence: 99%
See 1 more Smart Citation